The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/jocs.14139
|View full text |Cite|
|
Sign up to set email alerts
|

The learning curve effect on outcomes with frozen elephant trunk technique for extensive thoracic aorta disease

Abstract: Objective The purpose of this study was to analyze the learning curve effect on hospital mortality, postoperative outcomes, freedom from reintervention in the aorta and long‐term survival after frozen elephant trunk (FET) operation. Methods From July 2009 to June 2018, 79 patients underwent surgery with the FET technique. They had type A aortic dissection (acute 7.6%, chronic 33%), type B aortic dissection (acute 1.26%, chronic 34.2%), and complex thoracic aortic aneurysm (24%). 27.8% were reoperations and 43%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…These wide variations in mortality may be attributed to differences in experience in addition to the aggressiveness of the procedure. Dinato and associates divided their patients into two groups according to the operative date distribution ( 25 ). The results showed that earlier in-hospital mortality (from 2009 to 2014) was significantly higher than that later (from 2015 to 2018) (30.7 vs. 10%; P = 0.02) and indicated that operative outcomes improved as experience accumulated.…”
Section: Discussionmentioning
confidence: 99%
“…These wide variations in mortality may be attributed to differences in experience in addition to the aggressiveness of the procedure. Dinato and associates divided their patients into two groups according to the operative date distribution ( 25 ). The results showed that earlier in-hospital mortality (from 2009 to 2014) was significantly higher than that later (from 2015 to 2018) (30.7 vs. 10%; P = 0.02) and indicated that operative outcomes improved as experience accumulated.…”
Section: Discussionmentioning
confidence: 99%
“…The complexity of the procedure for aortic dissection results in longer durations of operation and extracorporeal circulation, leading to postoperative renal failure in a significant proportion of patients 88 . The rate of acute renal failure after FET has been reported around 40% in some studies, 26,57 while it was identified in less than 10% in other reports 60,61 . In a meta‐analysis of 4178 patients, 8 the pooled estimate of acute renal failure was 15.5% (95% CI, 11.9–20.1).…”
Section: Discussionmentioning
confidence: 99%
“…Of 64 studies reporting outcomes of patients included in this report 13–76 . The proportions of studies from Asia, Europe, and North America were 54.7%, 31.3%, and 10.9%, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…2,3 The prevalence of SCI is of particular importance, because the rates reported (4.7% in the current study of Preventza and colleagues, 1 5.1% in the study of Tian and colleagues, 2 and 5.0% in the report of Hanif and colleagues 3 ) are higher than those reported for the classic elephant trunk procedure, for 1-stage procedures performed without a stent graft, and for conventional aortic arch procedures. [3][4][5][6][7] Some important limitations of the current study that were acknowledged by Preventza and colleagues 1 deserve comment. Age of the patients was not analyzed separately.…”
Section: Nicholas T Kouchoukos MDmentioning
confidence: 99%
“…These data may not reflect how the device will perform in lessexperienced centers as the procedure gains more widespread use, as the learning curve for FET can have a significant impact on hospital mortality and midterm survival. 6 FET may increase risk of spinal cord ischemia with extended stent coverage and should be used cautiously in acute type A dissection. RCTs are needed to guide best practice as FET gains widespread use.…”
mentioning
confidence: 99%